Peran Pemerintah bagi Pertumbuhan Ekonomi Indonesia - Seran, Stefanus Robertus; Gomes, Paulina M. S.; Bria, Jeane Ivoni; Piri, Maria Selvania; Dima, Enike Tje Yustin (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
Economic growth remains a central benchmark in assessing national development, especially for emerging economies such as Indonesia. Despite its vast resources and demographic advantages, Indonesia continues to face structural challenges in achieving inclusive and sustainable growth. This study aims to analyze the role of government in promoting economic growth through strategic interventions in public investment, particularly in infrastructure, human capital development, MSME support, and fiscal governance. Using a qualitative literature review approach, the research synthesizes recent empirical findings from 2019 to 2024 drawn from national and international journal publications, policy reports, and institutional studies. The analysis is conducted through thematic categorization and comparative interpretation to explore how government-led policies impact GDP growth and the Human Development Index (HDI). The results show that targeted public spending in education, healthcare, and infrastructure significantly contributes to improving long-term economic productivity. Furthermore, fiscal policies are found to be most effective when accompanied by good governance practices, transparency, and institutional integrity. Government support for MSMEs and productive sectors also strengthens economic resilience, especially during periods of global uncertainty. The study concludes that integrated and accountable government interventions are essential for fostering inclusive, stable, and sustainable economic development in Indonesia.